Dog Training Handboook : A 10-Week Training Course - Smyth, Stella and Bregh-Roose, Sally (London HarpreCollins Publishers, 2001)
All dogs are happier with proper training, as are their owners. This handbook is based on the authors' 10-week training course, and aims to build up dog and trainer confidence step-by-step as each week progresses. It should transform a lead-pulling, disobedient dog into an obedient companion.
Include Illustration and Index
Keywords: Dogs--Training -- Dogs